Compliance of clinical microbiology laboratories with recommendations for the diagnosis of bloodstream infections: Data from a nationwide survey in Italy. Issue 4 (3rd February 2020) - Arena, Fabio; Argentieri, Marta; Bernaschi, Paola; Fortina, Giacomo; Kroumova, Vesselina; Pecile, Patrizia; Rassu, Mario; Spanu, Teresa; Rossolini, Gian Maria; Fontana, Carla
Abstract: In 2014, the Italian Working Group for Infections in Critically Ill Patient of the Italian Association of Clinical Microbiologists updated the recommendations for the diagnostic workflow for bloodstream infections (BSI). Two years after publication, a nationwide survey was conducted to assess the compliance with the updated recommendations by clinical microbiology laboratories. A total of 168 microbiologists from 168 laboratories, serving 204 acute care hospitals and postacute care facilities, were interviewed during the period January–October 2016 using a questionnaire consisting of nineteen questions which assessed the level of adherence to various recommendations. The most critical issues were as follows: (a) The number of sets of blood cultures (BC) per 1, 000 hospitalization days was acceptable in only 11% of laboratories; (b) the minority of laboratories (42%) was able to monitor whether BCs were over or under‐inoculated; (c) among the laboratories monitoring BC contamination (80%), the rate of contaminated samples was acceptable in only 12% of cases;(d) the Gram‐staining results were reported within 1 hr since BC positivity in less than 50% of laboratories. By contrast, most laboratories received vials within 2–4 hr from withdrawal (65%) and incubated vials as soon as they were received in the laboratory (95%). The study revealed that compliance with the recommendations is still partial. Further surveys will be needed to monitor the situation in the future. Abstract : We present the result of national survey during which microbiologists from 204 Italian hospitals have been interviewed on the application of guidelines concerning the proper use of blood cultures. Although the study showed some positive aspects, a full compliance with the guidelines is still far away, and more surveys will be needed to monitor the situation in the future.